Numerical simulation and analysis of the transition to turbulence in boundary layer flows - Yap, Quen Seng. (2011)
This paper attempts to strengthen the possibility to view the fluctuations of velocity during a laminar-turbulent transition as fractal time series as proposed by Vladimir V. Kulish[1]. Multifractal time series analysis using fractal dimensions, Jeffreys divergence measure and Hurst exponent was applied on a laminar-turbulent transition boundary layer flow over a flat plate. The analysis uses real laminar-turbulent transition flow signals instead of hypothetical signals used by Vladimir V. Kulish. The analysis results of real and hypothetical signals were compared. The real signals showed multifractal properties via fractal dimensions, memory-traits via Jeffreys divergence measure and predictability via Hurst exponent. The analysis showed agreement with the method proposed by Vladimir V. Kulish. Multifractal time series analysis has high potential in analysing laminar-turbulent transitions.